Cloud computing adoption factors and business value determinants - Kyriakou, Niki (2019)
Cloud Computing (CC) emerges a new disruptive paradigm of sourcing the ICT services required by firms in order to support their processes and activities, quite different from the dominant one. In the existing ‘on-premises’ ICT services provision paradigm these services are produced primarily internally, based on assets (hardware and software) owned by the firm, installed in its premises, and administered and supported by its own ICT personnel. In contrast, in the new CC paradigm these ICT services are produced externally, at the CC services providers’ premises, using assets owned, administered and supported by them, and are delivered to the client firm over the Internet. The US National Institute for Standards and Technology (NIST) defines CC as “a model for enabling ubiquitous, convenient, on-demand network access to a shared pool of computing resources (e.g., networks, servers, storage, applications) that can be rapidly provisioned and released with minimal management effort or service provider interaction”. Most of the research that has been conducted on the CC is dealing with its technological aspects, while much less research has been conducted on its organizational aspects. Most of this latter research focuses on CC adoption factors, based mainly on the ‘Technology, Organization and Environment’ (TOE) theory of technological innovation adoption. However, this CC adoption factors research has focused on the first and the third perspective of the TOE framework: the technological and environmental factors affecting CC adoption. On the contrary limited research has been conducted concerning the second perspective of the TOE framework: the organizational factors; the effects of only a small number of firm’s characteristics on CC adoption have been investigated. Furthermore, there has been considerable literature concerning the potential of CC to offer important business benefits to firms, which are associated mainly with ICT support costs reduction, provision of flexible cost-effective computing capacity for supporting firm’s growth, reduction of required ICT investment and conversion of them to operational costs, ubiquitous access capabilities using various types of devices, scalability, and also rapid and low cost ICT support of firm’s innovation activity (of both product/service and process innovations). However, there has been limited empirical research on the ‘real-life’ benefits firms gain from CC, in order to understand to what extent, the above benefits are realized by firms, and which factors determine the magnitude of them. This Ph.D. Dissertation aims to contribute towards filling the aforementioned important research gaps. Its main research objectives are:  To identify firms’ characteristics that positively or negatively influence the adoption of CC.  To identify factors that affect the magnitude of the benefits and in general the business value that firms obtain from CC. The present Ph.D. Dissertation makes the following contributions:  It empirically investigates and compares the effects of a set of firms’ strategies (ICT investment reduction, product/service innovation, process innovation), personnel characteristics (employment of ICT personnel, sufficiency of ICT skills of firm’s employees, previous experience of ICT outsourcing), and technological characteristics (sophistication of firm’s ICT infrastructure), which had not been dealt with in previous relevant literature, on firm’s CC adoption propensity.  It contributes to the research on the European North-South division, by comparing the effects of the factors mentioned previously on firms’ CC adoption propensity between the European North and the European South. It empirically investigates the effects of open innovation (meant as collaboration with other firms for the design and implementation of innovations), which is a major trend of modern economy, on firms’ propensity to adopt CC.  It empirically investigates the effects of firms’ hard and soft ICT capital on the benefits they gain from CC.  It empirically investigates the effects of CC adoption management actions (contractual and relational governance of the relationships between firms and CC service providers, as well as adaptations in firm’s ICT skills and organization) on the benefits firms gain from CC The research presented in this Ph.D. Dissertation has provided interesting and practically relevant conclusions about the effects of different kinds of firm’s characteristics on the propensity to adopt CC. In particular, the sophistication of firm’s ICT infrastructure has been found to have a strong positive effect on firms’ propensity to adopt CC, Similarly, strategies of ICT investment reduction increase firms’ CC adoption propensity; however, this does not hold for innovation strategies, which do not affect CC adoption propensity. These indicate that firms (at least of the glass, ceramic and cement sectors, from which the data for this part of our research have been collected) view CC as a means of reducing ICT investment, but not as a means of supporting innovation. Furthermore, the employment of specialized ICT personnel and previous experience of ICT outsourcing were found to positively affect firm’s propensity to adopt CC. Despite the expectations that CC would be more beneficial for smaller than larger firms, we could not find any significant effect of size on the propensity of CC adoption in the sectors investigated in this study. Finally, the ICT skills of firm’s employees and the price and quality competition it faces do not affect the propensity to adopt CC. Also, our results indicate that different national contexts may have a significant effect on CC adoption determinants. In particular, we have found that in Southern European firms the adoption of a CC investment reduction strategy and the interest in new ICT (such as data warehousing, data mining, mobile services) affect positively CC adoption propensity. In contrast, for Northern European firms, it is the adoption of innovation strategy, as well as the electronic cooperation with other firms that affect CC adoption propensity positively; this reveals a quite different perception of CC in comparison with the Southern European firms. Finally, our results provide evidence about a relationship between two important trends of modern economy, the open innovation and the CC. In particular, the inter- organizational collaboration with other firms for the design of innovations impacts positively the propensity for CC adoption; also, the use of ICT in order to support such collaborations has an even stronger positive effect on firm’s propensity to adopt CC. Highly interesting and practically relevant are the conclusions of the second part of the research presented in this Ph.D. Dissertation, concerning the determinants of the benefits/business value that firms obtain from CC. In particular, four out of the six examined types of firm’s ICT hard and soft capital have been found to contribute to generating higher benefits from CC model: ICT strategic alignment, ICT infrastructure sophistication, internal ICT relationship, and internal capability for rapid implementation of various interconnections/integrations of existing firm’s IS. Finally, all examined four CC adoption management actions impact positively the benefits firms obtain from CC usage. The adaptation of firm’s ICT skills has the strongest positive impact on CC benefits, followed by the relational governance of firm’s relationships with its CC services providers. This result indicates that though CC services are a simple form of ICT outsourcing, based on the remote provision of highly standardized and minimally customizable ICT services, which are easily accessible in a self-service mode, with minimal interaction with their service provider, the development of a relationship with CC service providers continues to be important. Lower and of similar magnitude are the positive effects of the contractual governance of firm’s relationships with its CC services providers, and the adaptation of ICT organization within the firm, on CC benefits. Therefore, having detailed and comprehensive contracts with the CC service providers, has a positive impact on the benefits obtained from CC, though this impact is lower than the one of the relational governance (at least in the Greek national context, from which the firm level data for this second part of our research have been collected). Also, positive impact on CC benefits has the adaptation of the organization of ICT in the firm as well, however lower than the one of the adaptation of its ICT skills. In particular, the development of a strategic approach to CC exploitation, as well as specific processes for managing it, the adaptation of the role of firm’s ICT unit to the needs of the CC paradigm, and the decentralization of CC related decisions to some extent from the ICT unit to firm’s business units, lead to more benefits from CC.